Sosialisasi penyusunan bahan ajar sebagai upaya peningkatan kompetensi guru dalam pembelajaran - Rusmaini, Rusmaini; Holisoh, Ade; Sholeh, Badrus (Penamas: Journal of Community Service, 2025)
The quality of education greatly depends on the availability of relevant, contextual, and high-quality learning materials. As the frontline actors in the learning process, teachers are expected to possess the ability to develop instructional materials that align with both the characteristics of their students and the prevailing curriculum. However, field observations indicate that many teachers still lack optimal skills in this area, both in terms of conceptual understanding and practical application in the classroom. In response to this issue, this community service program was designed to enhance teachers’ understanding, skills, creativity, and innovation in developing instructional materials. The program was implemented through a series of activities, including orientation, training, and on-site mentoring for teachers at SMAN 21, Tangerang Regency. The methods employed were participatory, incorporating hands-on practice and reflective discussion. The results of the program indicate a significant improvement in teachers’ ability to develop more varied and pedagogically appropriate instructional materials. This activity makes a positive contribution to enhancing teacher professionalism and the quality of the learning process in schools.